Koch’s abdomen- management of surgical complications and outcomes at a remote hill area tertiary care center - Keshri, Amit; Kumar, Anil; Prakash, Sanjeev; Singh, Khem Pal (International Surgery Journal, 2019)
Background: Abdominal tuberculosis needs surgical intervention in a subset of patients; both in emergency and elective settings, requiring surgeons to be familiar with its varied and non-specific modes of presentation and their diagnosis and management. Methods: Patients of abdominal tuberculosis, having undergone surgical management at our Institute, VCSGGMS&RI-UT, between April 2015 to March 2019, numbering eighty (n= 80), were included in this concurrent observational study. Results: Middle age-group patients (20-50 years; 56.3%) with a male majority (73.8%) predominated. Reinfection/ relapse of tuberculosis infection might occur despite BCG immunisation (46.3%) and course of ATT (16.3%); complications like bowel obstruction (28; 35%), perforation etc. need laparotomy to effect relief, with stomy formation required (51.3%) frequently; inadequate recovery warranting a secondary/re-look laparotomy (15; 18.8%). Prolene suture for abdominal wound closure is advantageous with a lesser rate of complications and incisional hernia. Septicemia, multi-organ dysfunction, wound infection should be aggressively managed to prevent adverse outcomes, including death (10; 12.5%). Conclusions: Adequate, intensive and timely surgical intervention/laparotomy, with nutritional support, stomy care and concurrent ATT can result in prompt relief and speedy recovery of patients with abdominal tuberculosis.